Analisis Perilaku Konsumtif Pada Mahasiswa Penerima Beasiswa Bidikmisi-KIP Kuliah Angkatan 2020 UIN Raden Mas Said Surakarta - Putri Wardah Qurrotuaini; Dinda Puspitasari; Nafisatur Rohmah; Amalia Nurul Fatimah; Novi Yanti Hami Mullah (Academica: Journal of Multidisciplinary Studies, 2022)
This study aims to describe in depth the consumptive behavior of students receiving the Bidikmisi-Kip Lecture UIN Raden Mas Said Surakarta Class of 2020 in terms of the use of scholarship funds which are limited by three aspects, namely the food aspect, the fashion aspect, and the leisure aspect. This study uses a qualitative approach, the data in this study is primary data whose collection and analysis uses interview and observation techniques. The informants in this study consisted of 12 students who received the 2020 Bidikmisi-Kip College scholarship. The results showed that most of the 2020 Bidikmisi-Kip College students were able to manage funds well so that expenses did not exceed the limit. This is evidenced by the use of bidikmisi funds for simple daily life needs. Keywords: Bidikmisi Scholarship; Consumptive Behaviour; Fashion Aspect; Food Aspect; Leisure Aspects